Digital Liturgy and the Discernment of the Spirit: A Theological Framework for AI-Based Worship in Urban Indonesian Congregations - Siregar, Pangihutan (Cattleya Darmaya Fortuna, 2024)
The development of artificial intelligence (AI) technology presents both challenges and opportunities for church life, especially in the context of increasingly digital urban congregations. This article aims to develop a theological framework for digital liturgy and the discernment of the Spirit in the context of AI-based worship in Indonesia. Through a practical theological approach and contextual reflection, this study analyzes how AI can function as a liturgical tool without obscuring the spiritual, relational, and incarnational dimensions of Christian worship. Digital liturgy is understood not simply as a technological adaptation but also as a new space for the presence of the Holy Spirit that transcends physical boundaries and digital media. By referring to the concept of imago Dei in creation and pneumatological theology of the Spirit's presence, this article emphasizes the importance of spiritual discernment (discernment of spirits) so that the church does not lose its transcendence and community aspects in utilizing technology. The results of the study indicate that AI-based liturgy can be a legitimate and contextual form of worship if supported by critical, ethical, and pneumatological theological awareness. These findings pave the way for the development of a digital theology relevant to the Indonesian urban church in the era of artificial intelligence.